ANALISA KARAKTERISTIK BIODIESEL NYAMPLUNG - Darmanto, Seno; Sediono, Windu; Sarwoko, Sarwoko; Triyatno, Triyatno (Gema Teknologi, 2012)
Seno Darmanto, Windu Sediono, Sarwoko, Triyatno, in this paper explain that making of callophylum inophylum biodiesel fuel is done alkaly transesterification methode. Alkaly transesterification methode use methanol and basa (NaOH) of catalist. Procedur and setting of research that is consisted in material selection, treatment and setting of composition of methanol and catalist, operational temperature, reaction time, speed and mixer technical will effect quality and conversion level of callophylum inophylum biodiesel. And based data analyzer show that conversion of callophylum inophylum biodiesel can reach 90%. Properties of callophylum inophylum biodiesel show viscosity and flash point of callophylum inophylum biodiesel is ligthly higher than diesel fuel. And caloric value of callophylum inophylum biodiesel is slightly lower than diesel fuel. Key words: callophylum inophylum, biodiesel, properties, transesterification.